2009
DOI: 10.2320/matertrans.m2009056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vibration Timing on the Microstructure and Microtexture Formation of AZ91D Magnesium Alloys during Electromagnetic Vibration

Abstract: For an electric conductor in a static magnet, electromagnetic vibration (EMV) is activated to take place when an alternating current flows through the conductor in the direction perpendicular to that of the magnetic field. Following the principle, in the present study we solidified the AZ91D magnesium alloys at various vibration timing moments and then examined the microtexture and microtexture. It is revealed that the decrease of the starting vibration temperature in the mushy zone results in coarse microstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Our previous experimental results [16] revealed that EMV can take into effect to modify solidification structures when vibration is operated in mushy zone in which the primary solid and the remaining liquid coexist. In this hybrid region at high temperature, it has been well known that the electrical resistivity of a solid is much smaller than that of its counterpart liquid with similar composition.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous experimental results [16] revealed that EMV can take into effect to modify solidification structures when vibration is operated in mushy zone in which the primary solid and the remaining liquid coexist. In this hybrid region at high temperature, it has been well known that the electrical resistivity of a solid is much smaller than that of its counterpart liquid with similar composition.…”
Section: Discussionmentioning
confidence: 99%
“…The imposition of EMV above liquidus only, i.e., prior to the formation of a primary solid phase, or far below the liquidus with a great amount of fraction solid cannot produce refinement, as we have demonstrated in AZ91D magnesium alloys. 34) This is why the imposition in the present study commenced from 700°C and then through the semisolid region. This operation could guarantee that the present EMV was imposed effectively in refining solidification structures.…”
Section: (A)mentioning
confidence: 92%
“…It is noted that in the magnesium-based [50] and 7xxx aluminum alloys, [51] the weight fraction of the primary solid solution phase increases continuously from naught to unit once the alloys are cooled from liquidus to solidus. [24,41,42,52] Therefore, the primary solid phase crystallized just below the liquidus immerses and floats freely within the liquid pool. However, in the present alloys, the weight fraction of the Nd 2 Fe 14 B phase remains as high as 30 and 50 pct when the alloys are cooled from 700°C up to the eutectic temperature.…”
Section: A the Segmentation Of Nd 2 Fe 14 B Compounds During Emv Promentioning
confidence: 99%